2022
DOI: 10.1017/s0144686x2100177x
|View full text |Cite
|
Sign up to set email alerts
|

‘That is a place where I would want to go’: investigating digital nature to enhance social wellbeing among older adults

Abstract: Feelings of disconnectedness and social isolation among older adults are increasingly recognised as important challenges of our times. Interestingly, nature interaction can stimulate social connectedness and enhance perceived social support, indicating that nature can contribute to social wellbeing. However, nature may not always be around or accessible for older adults. In such cases, digital nature could provide an alternative means for enjoying nature's benefits. To identify limitations and restrictions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
(108 reference statements)
2
4
0
Order By: Relevance
“…In line with the aforementioned literature showing that older adults value logistic nature characteristics, such as well-maintained paths and places to sit down 36 and tended rather than wild nature, 24 arguably social aspiration and emotion scores are higher for participants who experienced a simulated walk through a tended, rather than wild, nature scene. As for the overall effect of nature interaction on feeling connected, we hypothesized an increase in feeling connected (pre- vs postexposure) for older adults in the present study.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…In line with the aforementioned literature showing that older adults value logistic nature characteristics, such as well-maintained paths and places to sit down 36 and tended rather than wild nature, 24 arguably social aspiration and emotion scores are higher for participants who experienced a simulated walk through a tended, rather than wild, nature scene. As for the overall effect of nature interaction on feeling connected, we hypothesized an increase in feeling connected (pre- vs postexposure) for older adults in the present study.…”
Section: Introductionsupporting
confidence: 85%
“…To further explore the impact of digital nature, a study was conducted in which older adults were exposed to digital nature designed based on research findings stressing the importance of spaciousness, safety, and comfort perceptions. 24 Using both quantitative and qualitative research methods, the present undertaking not only aims at pinpointing essential nature characteristics but also aims at identifying person-related and contextual variables that influence digital nature experience so as to provide initial guidelines for the implementation of digital nature in the lives of older adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that contact with nature is important for mental and social well-being [7,8] but that a certain "quantity" of interaction with nature is necessary, and that interaction with nature in digital space has a positive impact on people's well-being. This suggests that digital nature has great potential as a complementary strategy for people who are less mobile and have less frequent contact with nature or interactions with others, or for older people with mobility difficulties [9][10][11].…”
Section: Literature Review 21 Digital Nature: Digital Activities and ...mentioning
confidence: 99%